Rat Models of Metabolic Syndrome - Kwitek, Anne E (Methods in molecular biology (Clifton, N.J.), 2019)
Metabolic syndrome is a complex disorder that comprises several other complex disorders, including obesity, hypertension, dyslipidemia, and diabetes. There are several rat models that encompass component features of MetS. Some models are inbred strains selected for one or more traits underlying MetS; others are population models with genetic risk for MetS traits, are induced by environmental stressors such as diet, are spontaneous monogenic mutant models, or are congenic strains derived from a combination of these models. Together they can be studied to identify the genetic and physiological underpinnings of MetS to identify candidate genes or mechanisms for study in human MetS subjects.